The global return on capital, the Lucas Paradox and the Savings Glut - Daly, Kevin J. (Trinity College (Dublin, Ireland). Department of Economics, 2010)
This thesis is composed of three chapters related to the measurement, analysis and application of cross-country data on the return on physical capital. In Chapter 1, we derive a database of returns on physical capital that is fully consistent across the ten largest economies in the world (measured at 2005 US Dollar exchange rates). The database covers more than a quarter of a century of data in every case, with significantly earlier starting dates for some economies. The ten economies are the United States, Japan, Germany, China, UK, France, Italy, Canada, Spain and South Korea and, together, they account for more than 75% of global GDP. The estimates are based on data sourced directly from national statistical agencies, with adjustments made where necessary to ensure full cross-country consistency. Given a broad and consistent dataset, we can combine the individual measures of the return on capital (ROC) into an estimate of the global ROC for the first time, and conduct more comprehensive cross-sectional and time-series analysis.
Keywords: Economics, Ph.D.; Ph.D. Trinity College Dublin.